Chapter Antecedenti, origini e tratti caratterizzanti della Public History in Italia - TOMASSINI, LUIGI (Studi e saggi, 2019)
The essay outlines an excursus on the historical origins and precedents of Public History (PH) practices in Italy, around three main themes: Cultural Heritage; School and University; Territory. National conferences are analysed. There is a rapid and widespread development of PH, but characterized by its roots in a pre-existing reality.